Transgression in the novels of Esther Kinsky River and Rombo - Car, Milka (Poznańskie Studia Slawistyczne, 2025)
The writing of transnational border spaces marks the literary works of German author and Slavist Esther Kinsky, also a translator from Polish, Russian and English. Her novels River (Am Fluss, 2014) and Rombo (2022) will be analysed as atypical travel prose dedicated to descriptions of nature, especially humans’ influence on it. Kinsky’s texts will be read as novels and essays, marked by multiple transgressions of narrative boundaries, not only in terms of genre, in the interweaving of the traditional form of travel writing with fiction, reminiscences and reflections, but also in the questioning of materiality and subjectivity in the representation of post-industrial landscapes. The transgressive gesture of multiple transgressions as nature writing will be interpreted in accordance with ecocritical theory and principles of cultural topography.